2021
DOI: 10.1080/13557858.2021.1980772
|View full text |Cite
|
Sign up to set email alerts
|

What do women want? Migrant and refugee women’s preferences for the delivery of sexual and reproductive healthcare and information

Abstract: Objective: Migrant and refugee women experience inequities in sexual and reproductive health (SRH) care, reflected in the low uptake of SRH services. It is essential for healthcare providers and educators to be aware of women's preferences for SRH information and service delivery, to provide culturally responsive care. Identifying migrant and refugee women's preferences for SRH information and service delivery is the objective of this study. Design: This study investigated this issue, in communities of migrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Women from priority populations are keen to engage in opportunities to receive PCC, yet challenges exist in its delivery. 35 36 Education and training for health care providers have been suggested to enhance the delivery of equitable PCC. Therefore, further work in education and training for health care providers and implementation guideline tools that promote culturally appropriate provision of PCC are required to address the needs of priority populations.…”
Section: Discussionmentioning
confidence: 99%
“…Women from priority populations are keen to engage in opportunities to receive PCC, yet challenges exist in its delivery. 35 36 Education and training for health care providers have been suggested to enhance the delivery of equitable PCC. Therefore, further work in education and training for health care providers and implementation guideline tools that promote culturally appropriate provision of PCC are required to address the needs of priority populations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unprecedented circumstances of the COVID-19 pandemic, the present study needed to pivot to provide cervical screening health promotion using online videoconferencing. This is a novel way to provide cervical screening health promotion with CALD women [ 31 ]. Online delivery required fewer logistical components (i.e., no requirement for venue, catering, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy facilitates informed decision making, contributing to better health outcomes and empowerment [ 29 ]. Many CALD women recognise that they have inadequate knowledge about cervical screening and HPV vaccination, and have identified that is an area of health literacy they would like to improve [ 30 , 31 ]. There is a particular need for cervical screening health literacy programs given recent changes to the national cervical screening program in Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging men is also critical to enable them equitably support their partners' reproductive health and share responsibilities for healthy sexuality and reproduction (Barker et al, 2007). This is signi cant as refugee and migrant women and health care providers in recent research have called for greater engagement of men in SRH care (Hawkey et al, 2021;Mengesha et al, 2017). Furthermore, improved engagement of men in SRH is critical to promote and achieve gender equality and challenge harmful gender roles and attitudes that undermine women's SRH autonomy and rights and discourage men from seeking care (Bustamante-Forest & Giarratano, 2004; Shand & Marcell, 2021).…”
Section: Discussionmentioning
confidence: 99%